Semantic Field of Teacher Terms in Ta`lim al-Muta`'allim Book by Sheikh Al-Zarnuji - Wahdan Abdul Manan; Abdul Hadi; Zulli Umri Siregar; Anwer Rakan Shallal (PPPBA, 2024)
Ta'lim Muta'allim is a book written by Shaykh al-Zarnuji that delves into the manners and guidelines for studying according to Islamic teachings. Throughout the text, the term